Test stewardship, frequency and fidelity: Impact on reported hospital-onset Clostridioides difficile. (22nd April 2019) - Fleming, Michele S.; Hess, Olivia; Albert, Heather L.; Styslinger, Emily; Doll, Michelle; Nguyen, Huong Jane; McAulay-Kidd, Susan; Hemphill, Robin R.; Srivastava, Tara; Cooper, Kaila D.; Stevens, Michael P.; Bearman, Gonzalo
Abstract: We assessed the impact of an embedded electronic medical record decision-support matrix (Cerner software system) for the reduction of hospital-onset Clostridioides difficile . A critical review of 3, 124 patients highlighted excessive testing frequency in an academic medical center and demonstrated the impact of decision support following a testing fidelity algorithm.